WOCAT SLM Technology: “ICT2Scale – supporting smallholder farmers with cellphone-based services via SMS [Tunisia]” - Verbist, Joren; Rudiger, Udo; Frija, Aymen; Idoudi, Zied; Dhehibi, Boubaker; Ouerghemmi, Hassen (The Global Database on Sustainable Land Management (SLM) of WOCAT, 2024)
The WOCAT publication describes the use of ICT for agricultural extension including SMS, applications and e-learning modules.